Pengaruh Drama India di Antv Terhadap Perilaku Imitasi Ibu-Ibu Rumah Tangga di Kelurahan Kedung Baruk Surabaya (Jurnal Kajian Media, 2017)
This research is based on Indian drama in ANTV toward housewifes imitation behavioral in Kedung Baruk district at Surabaya city. The purpose of this research is to know how much impact of imitation behavioral that shown by housewifes in Kedung baruk district at Surabaya city. This research is using quantitative with correlation approach, which this correlation analysis approach is used for knowing the connection between one variable with the other variables. The method of data analyze that is used to describe one by one. Keywords: Imitation behavior, Indian drama at ANTV, Housewife